PENGARUH ESG DISCLOSURE TERHADAP MARKET VALUE DAN ECONOMIC PROFIT PERUSAHAAN - Yunita Yudiputri; Dwi Cahyo Utomo (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of ESG Disclosure on Market Value and Economic Profit. The independent variable in this study, ESG Disclosure, is measured using the ESG Disclosure Score published by Bloomberg Terminal. The dependent variables Market Value, is measured using Tobin’s Q ratio and Economic Value Added (EVA). The population in this study consists of companies listed on the LQ45 index consecutively from 2020 to 2024. Sampling was conducted using purposive sampling, which is sampling based on certain criteria that have been determined in advance. The total number of companies sampled was 100. The analysis method used in this study was panel data regression with random-effects and common-effects models. The results of the study show that ESG Disclosure does not affect Market Value and Economic Profit, and show that ESG Disclosure weakens Tobin’s Q and EVA.